Process Mining: An Effort to Address Speech Delay in 5-Year-Old Children - Arina Athiyallah; Enver F. Omerovic; Mohamed Esse Mohamoud; Hasan Basri; Kusnadi Kusnadi; Nur Fadlan (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
TThe management of speech delay in 5-year-old children remains less effective because it has not fully utilized structured, integrated process data analysis. This study aims to assess the effectiveness of process mining in enhancing language skills in children with speech delay in a clear, systematic, and integrated manner. The research employed an experimental method with a pretest-posttest design and used the Wilcoxon test to evaluate significance. The results demonstrate that applying process mining has a positive impact on children’s language abilities. Initial pretest scores showed a total of 120 points with an average of 20. After the intervention, posttest scores increased, reaching a total of 181 points with an average of 30.2. All children improved their scores, with increases ranging from 9 to 11 points. Children 1, 2, and 4 had the highest increase of 11 points, while Children 3 and 5 each increased by 9 points, and Child 6 increased by 10 points. The Wilcoxon test yielded a significance value of 0.007, which is below 0.05, indicating a statistically significant difference. This confirms that process mining effectively enhances children’s language skills. Conclusion: Process mining has proven to be an effective method for significantly and measurably improving the language abilities of 5-year-old children with speech delay. Significance: This study advances data-driven speech delay therapy methods that are effective, measurable, and suitable for elementary school settings.